Self-adhesive film and optical display device including the same

The adhesive film, composed of a (meth)acrylic copolymer, chain transfer agent, photoinitiator, and UV absorbers, addresses the need for UV protection and mechanical properties in optical display devices without polarizing plates, ensuring reliable adhesion and bending reliability.

JP2025003402APending Publication Date: 2025-01-09SAMSUNG SDI CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024099872
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-21
Filing Date
2024-06-20
Publication Date
2025-01-09

AI Technical Summary

Technical Problem

Adhesive films for optical display devices without polarizing plates need to protect organic light-emitting elements from UV damage while providing appropriate elastic modulus and peel force in both partially cured and post-cured states.

Method used

The adhesive film comprises a (meth)acrylic copolymer, a chain transfer agent, a photoinitiator, and a mixture of UV absorbers, including an indole UV absorber as a first UV absorber and a triazine-based UV absorber, to achieve the desired elastic modulus, peel force, and UV protection.

Benefits of technology

The adhesive film effectively protects organic light-emitting devices from UV damage, maintains appropriate elastic modulus and peel force before and after post-curing, and ensures reliable adhesion and bending reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025003402000001
    Figure 2025003402000001
  • Figure 2025003402000002
    Figure 2025003402000002
  • Figure 2025003402000003
    Figure 2025003402000003
Patent Text Reader

Abstract

To provide a self-adhesive film in a partially cured state, the self-adhesive film capable of imparting an elastic modulus and a peel force in an appropriate range, capable of imparting an elastic modulus and a peel force in an appropriate range even in postcure, and capable of protecting an organic light-emitting element from a damage by UV.SOLUTION: A self-adhesive film includes a (meth)acrylic copolymer, a chain-transfer agent, a photoinitiator and a mixture of UV absorbers. The mixture of UV absorbers includes, as a first UV absorber, an indole-based UV absorber, and, as a second UV absorber, one or more of 2-hydroxyphenyl-s-triazine-based, being a triazine-based UV absorber, and 2-(5-chloro-2H-benzotriazol-2-yl)-6-(1,1-dimethylethyl)-4-methyl phenol, being a benzotriazole-based UV absorber. An optical display device includes the self-adhesive film.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive film and an optical display device including the same. [Background technology]

[0002] In recent years, attempts have been made to remove the polarizing plate used in optical display devices. This can provide the effects of making the optical display device thinner, reducing manufacturing costs, and improving processability. Therefore, the adhesive film must provide the functions that the conventional polarizing plate achieved.

[0003] In an optical display device without a polarizing plate, an adhesive film laminated on the upper surface of an organic light emitting device panel (the surface through which external light is incident on the organic light emitting device panel) needs to protect the organic light emitting device from damage caused by UV rays.

[0004] Depending on the composition forming the adhesive film, the adhesive film may be partially cured at a predetermined curing rate before being bonded to the organic light emitting device panel to prepare an adhesive film, and the adhesive film may then be bonded to the organic light emitting device panel and post-cured in the state of being bonded to the organic light emitting device panel. Compared to a case where the adhesive film is bonded to the organic light emitting device panel in a completely cured state, an adhesive film prepared by partially curing has a relatively low storage modulus. Therefore, the adhesive film prepared by partially curing can be more easily bonded to the organic light emitting device panel. Meanwhile, photocuring may be preferred since the post-curing is performed on the organic light emitting device panel.

[0005] There is a need for an adhesive film that protects organic light-emitting devices from UV damage while at the same time providing an appropriate range of elastic modulus and peel strength in a partially cured state and also providing an appropriate range of elastic modulus and peel strength after post-cure.

[0006] The background art of the present invention is disclosed in Patent Document 1. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Korean Patent Publication No. 2007-0055363 Summary of the Invention [Problem to be solved by the invention]

[0008] According to one embodiment, an adhesive film is provided that is in a partially cured state and provides an appropriate range of elastic modulus and peel strength, and also provides an appropriate range of elastic modulus and peel strength even after post-curing, thereby protecting an organic light-emitting element from UV damage.

[0009] According to one embodiment, an adhesive film is provided. [Means for solving the problem]

[0010] The adhesive film comprises a mixture of a (meth)acrylic copolymer, a chain transfer agent, a photoinitiator, and a UV absorber, the mixture of UV absorbers comprising an indole-based UV absorber as a first UV absorber, and one or more of a 2-hydroxyphenyl-s-triazine-based triazine-based UV absorber and a 2-(5-chloro-2H-benzotriazol-2-yl)-6-(1,1-dimethylethyl)-4-methylphenol-based benzotriazole-based UV absorber as a second UV absorber.

[0011] According to another embodiment, an optical display device is provided.

[0012] The optical display device includes a cured product of the adhesive film. Effect of the Invention

[0013] The adhesive film is partially cured and provides an appropriate range of elastic modulus and peel strength, and even after post-curing, provides an appropriate range of elastic modulus and peel strength, protecting the organic light-emitting device from UV damage. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will now be described in detail with reference to the embodiments so that those skilled in the art can easily carry out the embodiments to which the present invention pertains. As such, the present invention may be embodied in many different forms and should not be construed as limited to the embodiments set forth herein.

[0015] The terms used herein are merely used to describe exemplary embodiments and are not intended to limit the present invention. Unless otherwise clearly indicated in the context, singular expressions include plural expressions.

[0016] In this specification, "post-curing" refers to photocuring, and photocuring is carried out by applying UV light of 315 nm to 400 nm in wavelength at 1000 mJ / cm to an adhesive film (for example, 100 μm to 200 μm thick) using a metal halide lamp. 2 ~3000mJ / cm 2 , preferably 2000 mJ / cm 2 ~3000mJ / cm 2 The curing step may include irradiating the resin with a light amount of 1000 to 2000 nm.

[0017] In this specification, "partial curing" refers to photocuring, and photocuring is performed by applying a composition for adhesive films to one side of a release film in a predetermined thickness, and applying UV light of 315 nm to 400 nm in wavelength at 300 mJ / cm using a BL lamp (black light lamp). 2 ~2000mJ / cm 2 The curing step may include irradiating the resin with a light amount of 1000 to 2000 nm.

[0018] In this specification, "glass transition temperature of homopolymer" means the glass transition temperature (Tg) measured for a homopolymer of a monomer to be measured using DSC Discovery by TA Instruments, Inc. Specifically, the homopolymer of a monomer to be measured is heated to 180°C at a rate of 20°C / min, then gradually cooled to -100°C, and heated to 100°C at a rate of 10°C / min to obtain data on an endothermic transition curve, and the inflection point of the endothermic transition curve is determined as the glass transition temperature.

[0019] In this specification, the "average particle size" of organic nanoparticles refers to the particle size of organic nanoparticles expressed as a Z-average value measured in an aqueous or organic solvent using a Zetasizer nano-ZS device manufactured by Malvern, and the particle size confirmed by SEM / TEM observation.

[0020] In this specification, "(meth)acrylic" means acrylic and / or methacrylic.

[0021] In this specification, the "refractive index" is a value measured in the visible light region, for example at a wavelength of 550 nm.

[0022] In this specification, "light transmittance" means single-piece light transmittance.

[0023] In this specification, when describing a numerical range, "X to Y" means at least X and at most Y (X≦and≦Y).

[0024] One embodiment is for an optical clear adhesive (OCA) film.

[0025] According to one embodiment, a pressure-sensitive adhesive film is provided, and the pressure-sensitive adhesive film is obtained by partially curing a composition for a pressure-sensitive adhesive film described below. As described below, the pressure-sensitive adhesive film can be laminated to an adherend (e.g., a panel for an optical display device) in an optical display device without a polarizing plate, and then post-cured, so that the pressure-sensitive adhesive film can be finally laminated and fixed to the panel.

[0026] In one embodiment, the "post-cured adhesive film" refers to an adhesive film having a ratio of the following Equation 1 of 100%:

[0027] The adhesive film is in a pre-post-cure state and has a different storage modulus at the same measurement temperature compared to the post-cure adhesive film, which allows one to determine that the adhesive film has a different cure rate compared to the post-cure adhesive film.

[0028] In one embodiment, the pressure-sensitive adhesive film may have a storage modulus ratio calculated by the following mathematical formula 1 of 80% or more and less than 100%, for example, 80% to 95%.

[0029] [Formula 1] Storage modulus ratio = A / B x 100 (In formula 1, A is the storage modulus (unit: kPa) of the adhesive film at 25°C, B is the storage modulus (unit: kPa) of the post-cured adhesive film at 25°C.

[0030] In this regard, the adhesive film may have a photocuring rate of 80% or more and less than 100%, for example, 90% to 99%. The "photocuring rate" can be measured by the following method.

[0031] The adhesive film composition was measured using FT-IR (NICOLET 4700, Thermo) at 1635 cm -1 Near (C=C), 1720cm -1 The intensity of the absorption peak near (C=O) is measured. The composition is applied to a glass substrate, and UV rays with wavelengths of 315 nm to 400 nm are irradiated at 1000 mJ / cm using a BL lamp (black light lamp). 2 The adhesive film was then photocured by irradiating it with a light intensity of 1635 cm to obtain an adhesive film specimen of 20 cm x 20 cm x 3 μm (width x length x thickness). -1Near (C=C), 1720cm -1 The intensity of the absorption peak near (C=O) is measured. The photocuring rate is calculated by the following formula 2.

[0032] [Formula 2] Photocuring rate (%)=|1-(C / D)|×100 (In formula 2, C is 1720 cm for the adhesive film. -1 Intensity of absorption peaks near 1635 cm -1 is the ratio of the intensities of the absorption peaks in the vicinity D is 1720 cm for the adhesive film composition -1 Intensity of absorption peaks near 1635 cm -1 (The ratio of the intensities of the absorption peaks in the vicinity of the

[0033] Even though the pressure-sensitive adhesive film is in a partially cured state, it has a storage modulus and peel strength within an appropriate range, and can therefore be attached to an adherend with high reliability.

[0034] In one embodiment, the pressure-sensitive adhesive film may have a storage modulus of 150 kPa or less, for example, 10 kPa to 150 kPa, at 25° C. Within this range, the pressure-sensitive adhesive film has good viscoelasticity after post-curing and excellent bending reliability.

[0035] In one embodiment, the pressure-sensitive adhesive film may have a storage modulus of 100 kPa or less, for example, 10 kPa to 50 kPa, at 60° C. Within this range, the pressure-sensitive adhesive film has good viscoelasticity after post-curing and excellent bending reliability.

[0036] In one embodiment, the adhesive film may have a peel strength from a glass plate of 4000 gf / inch or more, for example, 4000 gf / inch to 6000 gf / inch. In this range, the adhesive film is not easily peeled off from the panel after post-curing, and therefore has excellent reliability.

[0037] The pressure-sensitive adhesive film has a storage modulus and peel strength in an appropriate range after post-curing, so that it can be attached and fixed to an adherend with high reliability and can provide excellent bending reliability even when repeatedly bent.

[0038] In one embodiment, the pressure-sensitive adhesive film may have a storage modulus of 150 kPa or less, for example 10 kPa to 150 kPa, at 25° C. after post-curing. Within this range, the pressure-sensitive adhesive film has good viscoelasticity after post-curing and excellent bending reliability.

[0039] In one embodiment, the pressure-sensitive adhesive film may have a storage modulus of 50 kPa or less, for example 10 kPa to 50 kPa, after post-curing at 60° C. In this range, the pressure-sensitive adhesive film has good viscoelasticity after post-curing and excellent bending reliability.

[0040] In one embodiment, the adhesive film may have a peel strength from a glass plate after post-curing of 4000 gf / inch or more, for example, 4000 gf / inch to 6000 gf / inch. In this range, the adhesive film is not easily peeled from the panel after post-curing, and therefore has excellent reliability.

[0041] The adhesive film has an effect of protecting the organic light emitting device from damage caused by UV. According to an embodiment, the adhesive film has a light transmittance in a predetermined wavelength range after post-curing, and can protect the organic light emitting device from damage caused by UV. Of course, the adhesive film has a light transmittance in a predetermined wavelength range before post-curing, and can protect the organic light emitting device from damage caused by UV.

[0042] In one embodiment, the adhesive film may have a light transmittance of 1% or less at a wavelength of 380 nm, for example, 0% or more and less than 1%, such as 0.01% to 0.5%, which can provide an effect of protecting the organic light emitting element from damage caused by UV.

[0043] In one embodiment, the adhesive film may have a light transmittance of 3% or less at a wavelength of 405 nm, for example, 0% or more and less than 3%, such as 0.01% to 2.5%, which can provide an effect of protecting the organic light emitting element from damage caused by UV.

[0044] Here, the "light transmittance at a wavelength of 380 nm" and the "light transmittance at a wavelength of 405 nm" are values ​​measured for the pressure-sensitive adhesive film and the post-cured pressure-sensitive adhesive film.

[0045] In one embodiment, the pressure-sensitive adhesive film may have a light transmittance of 70% or more at a wavelength of 430 nm, for example, 70% to 85%, or 75% to 80%. Within this range, the pressure-sensitive adhesive film can be used in optical display devices as a transparent pressure-sensitive adhesive film.

[0046] Here, the "light transmittance at a wavelength of 430 nm" is a value measured for the pressure-sensitive adhesive film and the post-cured pressure-sensitive adhesive film.

[0047] The adhesive film is produced by partially curing the adhesive film composition described below by photocuring, and the specific UV absorber described below contains an indole UV absorber as a first UV absorber, and one or more of 2-hydroxyphenyl-s-triazine, which is a triazine UV absorber, and 2-(5-chloro-2H-benzotriazol-2-yl)-6-(1,1-dimethylethyl)-4-methylphenol, which is a benzotriazole UV absorber, as a second UV absorber, in order to provide the above-mentioned light transmittance at wavelengths of 380 nm and 405 nm, respectively. In general, the UV absorber can reduce the curing rate by absorbing the UV irradiated during photocuring.

[0048] The adhesive film includes a first UV absorber and a second UV absorber.

[0049] The first UV absorber and the second UV absorber can partially cure a composition for adhesive films containing the (meth)acrylic copolymer described below to provide an adhesive film that provides the above-mentioned storage modulus and peel strength.

[0050] In addition, by including the second UV absorber together with the first UV absorber, the light transmittance at wavelengths of 380 nm and 405 nm can be significantly reduced compared to an adhesive film that does not include the second UV absorber but includes the same amount of the first UV absorber.

[0051] In addition, compared with an adhesive film containing the same amount of a first UV absorber and a different type of UV absorber from the second UV absorber, an adhesive film containing the first UV absorber and the second UV absorber can significantly reduce the light transmittance at wavelengths of 380 nm and 405 nm.

[0052] In addition, even if the adhesive film contains a first UV absorber, if the adhesive film contains a different type of UV absorber other than the second UV absorber, the performance of the UV absorption rate will be reduced, thereby reducing the effect of protecting the organic light-emitting element from damage, and the color uniformity of the adhesive film will be reduced, resulting in a deterioration in the reflective color quality.

[0053] In particular, the present invention can achieve the above-mentioned effects of the present invention for a pressure-sensitive adhesive film formed from a composition for pressure-sensitive adhesive film comprising a (meth)acrylic copolymer, a chain transfer agent, and a photoinitiator, which will be described below. Hereinafter, a pressure-sensitive adhesive film according to one embodiment will be described.

[0054] The adhesive film comprises a mixture of a (meth)acrylic copolymer, a chain transfer agent, a photoinitiator and a UV absorber, and the mixture of UV absorbers can comprise an indole-based UV absorber as a first UV absorber, 2-hydroxyphenyl-s-triazine which is a triazine-based UV absorber as a second UV absorber, and one or more of 2-(5-chloro-2H-benzotriazol-2-yl)-6-(1,1-dimethylethyl)-4-methylphenol as a benzotriazole-based UV absorber.

[0055] The (meth)acrylic copolymer may be a copolymer of a monomer mixture containing an alkyl group-containing (meth)acrylic monomer and a hydroxyl group-containing (meth)acrylic monomer.

[0056] The alkyl group-containing (meth)acrylic monomer can form the matrix of the adhesive film. The alkyl group-containing (meth)acrylic monomer may be an unsubstituted linear or branched alkyl group-containing (meth)acrylate having 1 to 20 carbon atoms. For example, the alkyl group-containing (meth)acrylic monomer may include one or more of 2-ethylhexyl (meth)acrylate, n-butyl (meth)acrylate, isooctyl (meth)acrylate, propyl (meth)acrylate, t-butyl (meth)acrylate, iso-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, and decyl (meth)acrylate, preferably one or more of 2-ethylhexyl (meth)acrylate, n-butyl (meth)acrylate, and isooctyl (meth)acrylate, more preferably 2-ethylhexyl acrylate and n-butyl acrylate.

[0057] The alkyl group-containing (meth)acrylic monomer may have a homopolymer glass transition temperature of −20° C. or lower, for example, −80° C. to −20° C., or −80° C. to −40° C. In this range, the folding properties of the PSA film at low temperatures and at high temperatures and high humidity can be easily improved.

[0058] The alkyl group-containing (meth)acrylic monomer may be contained in the monomer mixture at 10% by weight to 90% by weight, 20% by weight to 60% by weight, for example, 25% by weight to 55% by weight, 30% by weight to 50% by weight. Within this range, the folding properties of the adhesive film at low temperatures and at high temperatures and high humidity can be easily improved.

[0059] The hydroxyl group-containing (meth)acrylic monomer can provide the peeling force of the adhesive film.

[0060] The hydroxyl group-containing (meth)acrylic monomer may be a linear or branched (meth)acrylate containing one or more hydroxyl groups and having 1 to 10 carbon atoms. For example, the hydroxyl group-containing (meth)acrylic monomer may include one or more of 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate, but is not limited thereto.

[0061] The hydroxyl group-containing (meth)acrylic monomer may have a homopolymer glass transition temperature of 0° C. or lower, for example, −70° C. to 0° C., −60° C. to −10° C., or −50° C. to −10° C. Within this range, the peel strength and foldability of the adhesive film can be easily increased.

[0062] The hydroxyl group-containing (meth)acrylic monomer may be contained in the monomer mixture at 0.1% by weight to 30% by weight, for example, 1% by weight to 30% by weight, 5% by weight to 25% by weight, or 10% by weight to 25% by weight. Within this range, the peel strength and durability reliability of the adhesive film are further improved.

[0063] The monomer mixture may further comprise a (meth)acrylic or vinyl monomer having a high homopolymer glass transition temperature.

[0064] A (meth)acrylic or vinyl monomer having a high glass transition temperature of a homopolymer can increase the peel strength of an adhesive film and provide a cohesive strength enhancing effect.

[0065] In one embodiment, the (meth)acrylic or vinyl monomer having a high homopolymer glass transition temperature can have a higher glass transition temperature than the respective homopolymer glass transition temperatures of the alkyl group-containing (meth)acrylic monomer and the hydroxyl group-containing (meth)acrylic monomer. This increases the peel strength of the adhesive film and makes it easier to reach the storage modulus range compared to the case where only the alkyl group-containing (meth)acrylic monomer having a low homopolymer glass transition temperature or the hydroxyl group-containing (meth)acrylic monomer having a low homopolymer glass transition temperature is applied.

[0066] For example, a (meth)acrylic or vinyl monomer having a high homopolymer glass transition temperature may have a homopolymer glass transition temperature of 5° C. or higher, for example, 5° C. to 200° C., or 10° C. to 200° C. Within this range, the peel strength of the adhesive film is increased.

[0067] The (meth)acrylic or vinyl monomer having a high homopolymer glass transition temperature is not particularly limited in type, so long as it has the above-mentioned homopolymer glass transition temperature range.

[0068] According to one embodiment, the (meth)acrylic or vinyl monomer may be a nitrogen-containing (meth)acrylic or vinyl monomer to facilitate dilution of the UV absorbent described below. Since the adhesive film can be produced using a solvent-free adhesive film composition, it is necessary to dilute the UV absorbent well in the adhesive film composition so that the adhesive film does not have high haze. The solvent-free adhesive film composition can provide an adhesive film having a uniform surface when applied for photocuring.

[0069] In one embodiment, the (meth)acrylic or vinyl monomer may include at least one of a (meth)acrylic or vinyl monomer having a heteroalicyclic group and a (meth)acrylic or vinyl monomer having an alicyclic group in order to maximize the dispersion effect of the UV absorber and to provide an effect of improving the peel strength.

[0070] In one embodiment, the (meth)acrylic or vinyl monomer may be a mixture of a (meth)acrylic or vinyl monomer having a heteroalicyclic group and a (meth)acrylic or vinyl monomer having an alicyclic group.

[0071] The (meth)acrylic or vinyl monomer having a heteroalicyclic group may be (meth)acryloylmorpholine, N-vinylpyrrolidone, or the like.

[0072] The (meth)acrylic or vinyl monomer having a heteroalicyclic group may be contained in the monomer mixture at 0.1% by weight to 30% by weight, for example, 1% by weight to 20% by weight, 5% by weight to 20% by weight, or 5% by weight to 15% by weight. Within this range, the peel strength and durability reliability of the adhesive film can be further improved.

[0073] The (meth)acrylic or vinyl monomer having an alicyclic group may be dihydrodicyclopentadienyl (meth)acrylate (for example, DCPA (dihydrodicyclopentadienyl acrylate)), isobornyl (meth)acrylate, or the like.

[0074] The (meth)acrylic or vinyl monomer having an alicyclic group may be contained in the monomer mixture at 0.1% by weight to 30% by weight, for example, 1% by weight to 20% by weight, 5% by weight to 20% by weight, or 5% by weight to 15% by weight. Within this range, the peel strength and durability reliability of the adhesive film can be further improved.

[0075] The (meth)acrylic or vinyl monomer having a high homopolymer glass transition temperature may be contained in the monomer mixture in an amount of 0 to 70% by weight, for example, 10 to 50% by weight. Within this range, the adhesive strength can be increased.

[0076] In one embodiment, the total content of the alkyl group-containing (meth)acrylic monomer, the hydroxyl group-containing (meth)acrylic monomer, and the (meth)acrylic or vinyl monomer having a high homopolymer glass transition temperature in the monomer mixture may be 80% by weight or more, for example, 80% by weight to 100% by weight. Within this range, the effect of the pressure-sensitive adhesive film of the present invention can be easily achieved.

[0077] The monomer mixture may further include an aromatic group-containing (meth)acrylic monomer.

[0078] The aromatic group-containing (meth)acrylic monomer can lower the dielectric constant of the PSA film before and after post-curing, or provide an effect of adjusting the refractive index.

[0079] The aromatic group-containing (meth)acrylic monomer may be a (meth)acrylic monomer containing a substituted or unsubstituted aryl group having 6 to 20 carbon atoms, or a substituted or unsubstituted arylalkyl group having 7 to 20 carbon atoms, such as benzyl (meth)acrylate, phenyl (meth)acrylate, naphthyl (meth)acrylate, phenoxy (meth)acrylate, benzylphenyl (meth)acrylate, etc.

[0080] The aromatic group-containing (meth)acrylic monomer may be contained in the monomer mixture in an amount of 0% by weight to 70% by weight, for example, 10% by weight to 40% by weight. Within this range, the dielectric constant can be lowered or the refractive index can be adjusted.

[0081] In one embodiment, the total amount of the alkyl group-containing (meth)acrylic monomer, the hydroxyl group-containing (meth)acrylic monomer, the (meth)acrylic or vinyl monomer having a high homopolymer glass transition temperature, and the aromatic group-containing (meth)acrylic monomer in the monomer mixture may be 95% by weight or more, for example, 95% by weight to 100% by weight. Within this range, the effect of the pressure-sensitive adhesive film of the present invention can be easily achieved.

[0082] The (meth)acrylic copolymer can be prepared from the monomer mixture described above using polymerization methods known to those skilled in the art.

[0083] The chain transfer agent is contained in the adhesive film and has the effect of increasing the fluidity of the (meth)acrylic copolymer by adjusting the weight average molecular weight of the (meth)acrylic copolymer. The chain transfer agent may include one or more of primary or secondary monofunctional thiol compounds or polyfunctional thiol compounds, thioglycolic acid compounds, thiocarbonyl compounds, and mercaptopropionic acid compounds.

[0084] Specific examples of the chain transfer agent include β-mercaptopropionic acid, 2-ethylhexyl-3-mercaptopropionate, n-octyl-3-mercaptopropionate, methoxybutyl-3-mercaptopropionate, stearyl-3-mercaptopropionate, trimethylolpropane tris(3-mercaptopropionate), tris-[(3-mercaptopropionyloxy)-ethyl]-isocyanurate, pentaerythritol tetrakis(3-mercaptopropionate), tetraethylene glycol bis(3-mercaptopropionate), dipentaerythritol hexakis(3-mercaptopropionate), 3,3′-thiodipropionic acid, dithiopropionic acid, laurylthiopropionic acid, thioglycolic acid, ammonium thioglycolate, monoethanolamine thioglycolate, and diammonium thioglycolate.

[0085] The chain transfer agent may be contained in an amount of 0.01 to 2 parts by weight, for example, 0.1 to 1 part by weight, 0.1 to 0.5 parts by weight, or 0.1 to 0.3 parts by weight, based on the solid content, relative to 100 parts by weight of the (meth)acrylic copolymer in the composition for adhesive films or the cured product of the (meth)acrylic copolymer in the adhesive film. Within this range, the effect of increasing fluidity by adjusting the weight average molecular weight of the (meth)acrylic copolymer and the effect of preventing a decrease in transparency of the adhesive film due to the inclusion of an excessive amount are achieved.

[0086] In this specification, the term "cured product of a (meth)acrylic copolymer" refers to a product in which a (meth)acrylic copolymer is partially cured by a photoinitiator.

[0087] The chain transfer agent may be contained in the pressure-sensitive adhesive film at 0.01% by weight to 2% by weight, for example, 0.01% by weight to 0.5% by weight. Within this range, the effect of increasing fluidity by adjusting the weight-average molecular weight of the (meth)acrylic copolymer and the effect of preventing a decrease in transparency of the pressure-sensitive adhesive film due to inclusion of an excessive amount are achieved.

[0088] The photoinitiator can cure the adhesive film composition to form an adhesive film and post-cure the adhesive film. Preferably, the photoinitiator can include a photoradical initiator.

[0089] The photoinitiator is not particularly limited as long as it can perform curing by light irradiation, etc. For example, the photoinitiator may be a benzoin-based, hydroxyketone-based, aminoketone-based, or phosphine oxide-based photoinitiator.

[0090] The photoinitiator may be contained in the composition for adhesive films in an amount of 0.1 to 2 parts by weight, for example, 0.1 to 1 part by weight, or 0.3 to 0.6 parts by weight, based on the solid content, relative to 100 parts by weight of the (meth)acrylic copolymer. Within this range, the composition for adhesive films is cured to form an adhesive film, and post-curing is also facilitated.

[0091] The photoinitiator may be contained in the adhesive film in an amount of 0.01% by weight to 5% by weight, for example, 0.01% by weight to 1% by weight, or 0.2% by weight to 0.6% by weight. Within this range, the adhesive film composition is cured to form an adhesive film, and post-curing is also facilitated.

[0092] The adhesive film includes an indole-based UV absorber as a first UV absorber.

[0093] The indole-based UV absorbent can reduce the light transmittance at the above-mentioned wavelength of 380 nm or 405 nm, so that when the adhesive film is applied to an optical display device, the adhesive film can prevent damage to the organic light-emitting element caused by UV.

[0094] The indole UV absorber may have a maximum absorption wavelength of 390 nm or more, specifically 390 nm or more and 400 nm or less, more specifically more than 390 nm and less than 400 nm. In this range, the UV transmittance is reduced by sufficiently absorbing light in the wavelength range of 420 nm or less, 400 nm to 420 nm, and 405 nm or less in the outside light, thereby reducing damage to the organic light-emitting element. The "maximum absorption wavelength" means the wavelength that shows the maximum absorption peak, that is, the wavelength that shows the maximum absorbance in the absorbance curve by wavelength. The "absorbance" can be measured by a conventional method known to those skilled in the art.

[0095] The indole-based UV absorber can include a compound of general formula 1: [General formula 1] [ka] (In Equation 1, R 1 represents hydrogen or a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms; R 2 represents hydrogen or a substituted or unsubstituted aryl group having 6 to 20 carbon atoms; R 3 represents hydrogen or a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms; R 4 represents hydrogen, a cyano group (CN), or a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms; R 5 is a cyano group or -(C=O)OR 6 (At this time, R 6 represents a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 20 carbon atoms).

[0096] Specifically, R 1 is an alkyl group having 1 to 5 carbon atoms, specifically a methyl group; R 2 is an aryl group having 6 to 10 carbon atoms, specifically a phenyl group; R 3 is hydrogen or an alkyl group having 1 to 5 carbon atoms, specifically hydrogen, R 4 is a cyano group, R 5 is a cyano group or -(C=O)-OR 6 (At this time, R 6 represents a substituted or unsubstituted alkyl group having 1 to 5 carbon atoms).

[0097] More specifically, the indole UV absorber may include a compound of the following general formula 1-1 or the following general formula 1-2: [General formula 1-1] [ka] [General formula 1-2] [ka]

[0098] In one embodiment, the indole UV absorber may be an absorber having a melting point of 100° C. or higher, specifically 140° C. to 220° C., and being in a solid phase at room temperature.

[0099] The indole UV absorber can be contained in the (meth)acrylic copolymer in the composition for adhesive film or in the adhesive film in an amount of 0.01 to 0.5 parts by weight, for example, 0.05 to 0.5 parts by weight, 0.05 to 0.3 parts by weight, based on the solid content, relative to 100 parts by weight of the cured product of the (meth)acrylic copolymer. Within this range, it is possible to exert the effect of protecting the organic light-emitting element from damage caused by UV and preventing a decrease in the curing rate during photocuring.

[0100] The indole UV absorber may be contained in the adhesive film at 0.01% by weight to 10% by weight, for example, 0.01% by weight to 5% by weight, or 0.01% by weight to 3% by weight. Within this range, the organic light-emitting element can be protected from damage caused by UV rays, and the effect of preventing a decrease in the curing rate during photocuring can be achieved.

[0101] The adhesive film contains at least one of the following: 2-hydroxyphenyl-s-triazine-based absorber, which is a triazine-based UV absorber, as a second UV absorber; and 2-(5-chloro-2H-benzotriazol-2-yl)-6-(1,1-dimethylethyl)-4-methylphenol, which is a benzotriazole-based UV absorber. This specific second UV absorber absorbs UV light to protect the organic light-emitting element from damage, and can easily reach the above-mentioned elastic modulus and peeling force when the adhesive film composition is partially cured, and can significantly reduce the light transmittance at wavelengths of 380 nm and 405 nm in combination with the first UV absorber.

[0102] In one embodiment, the triazine-based UV absorber may be a compound of general formula 2: [General formula 2] [ka]

[0103] The triazine UV absorber may be prepared by methods known to those skilled in the art or may be used under the trade name Tinuvin 477.

[0104] The benzotriazole UV absorber may be a compound of the following general formula 3: [General formula 3] [ka]

[0105] Benzotriazole UV absorbers can be prepared by methods known to those skilled in the art or can be used under the trade name Tinuvin 326.

[0106] The second UV absorbent may be contained in the adhesive film composition in an amount of 0.01 to 5 parts by weight, for example 0.1 to 5 parts by weight, based on the solid content, relative to 100 parts by weight of the (meth)acrylic copolymer or the cured product of the (meth)acrylic copolymer. Within this range, the second UV absorbent can absorb UV light and provide an effect of protecting the organic light-emitting element from damage.

[0107] The second UV absorbent can be contained in the adhesive film in an amount of 0.01% by weight to 5% by weight, for example, 0.05% by weight to 5% by weight, or 0.1% by weight to 5% by weight. Within this range, the second UV absorbent can absorb UV light and provide the effect of protecting the organic light-emitting element from damage.

[0108] In order to perform photocuring for partial curing by UV absorbing effect and UV initiated reaction, the weight ratio of the content between the photoinitiator and the second UV absorbent in the adhesive film or the composition for the adhesive film according to the formula 3 is adjusted to 0.06 to 6, preferably 0.1 to 3. In this range, the UV absorbing effect can be achieved while the UV initiated photocuring reaction occurs.

[0109] [Formula 3] Weight ratio = photoinitiator / second UV absorber

[0110] The total of the first UV absorbent and the second UV absorbent can be contained in the total UV absorbent contained in the adhesive film at 95% by weight or more, for example, 95% by weight to 100% by weight. In this range, the effect of the present invention can be easily realized, and the problem of increased haze of the adhesive film due to the addition of an excessive amount of UV absorbent is eliminated. Here, "total UV absorbent" means a normal absorbent known to those skilled in the art to absorb light in the UV absorption region.

[0111] The first UV absorber and the second UV absorber may be contained in the pressure-sensitive adhesive film in a weight ratio of 1:0.5 to 1:90, preferably 1:0.5 to 1:85. Within this range, the effect of the UV absorber of the present invention can be easily achieved.

[0112] The adhesive film may further include a crosslinking agent.

[0113] The crosslinking agent can increase the degree of crosslinking of the composition for a pressure-sensitive adhesive film, thereby increasing the mechanical strength of the pressure-sensitive adhesive film.

[0114] The crosslinking agent can include a multifunctional (meth)acrylate that can be cured with active energy radiation. For example, the crosslinking agent can be 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, neopentyl glycol adipate di(meth)acrylate, dicyclopentanyl di(meth)acrylate, caprolactone-modified dicyclopentenyl di(meth)acrylate, ethylene oxide-modified di(meth)acrylate, di(meth)acryloxyethyl isocyanurate, allylated cyclopentanyl di(meth)acrylate, di ... Di(meth)acrylates such as hexyl di(meth)acrylate, tricyclodecane dimethanol (meth)acrylate, dimethylol dicyclopentane di(meth)acrylate, ethylene oxide modified hexahydrophthalic acid di(meth)acrylate, tricyclodecane dimethanol (meth)acrylate, neopentyl glycol modified trimethylpropane di(meth)acrylate, adamantane di(meth)acrylate, or 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, etc. functional acrylates; trimethylolpropane tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, propionic acid modified dipentaerythritol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, propylene oxide modified trimethylolpropane tri(meth)acrylate, trifunctional urethane (meth)acrylate, or tris(meth)acryloxyethyl isocyanurate; diglycerin tetra(meth)acrylate, or penta Examples of the functional acrylate include, but are not limited to, tetrafunctional acrylates such as erythritol tetra(meth)acrylate; pentafunctional acrylates such as dipentaerythritol penta(meth)acrylate; and hexafunctional acrylates such as dipentaerythritol hexa(meth)acrylate, caprolactone-modified dipentaerythritol hexa(meth)acrylate, or urethane(meth)acrylate (e.g., a reaction product of an isocyanate monomer and trimethylolpropane tri(meth)acrylate).

[0115] The crosslinking agent may be contained in the composition for adhesive film in an amount of 0 to 5 parts by weight, for example 0.01 to 1 part by weight, based on the solid content, per 100 parts by weight of the (meth)acrylic copolymer or the cured product of the (meth)acrylic copolymer. Within this range, other physical properties of the adhesive film are not affected, and the mechanical strength of the adhesive film can be increased.

[0116] The adhesive film may further contain a silane coupling agent.

[0117] The silane coupling agent can further increase the peeling force of the adhesive film to the adherend. The silane coupling agent can include ordinary types known to those skilled in the art. For example, the silane coupling agent can include one or more selected from the group consisting of silicon compounds having an epoxy structure such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; polymerizable unsaturated group-containing silicon compounds such as vinyltrimethoxysilane, vinyltriethoxysilane, (meth)acryloxypropyltrimethoxysilane; amino group-containing silicon compounds such as 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane; and 3-chloropropyltrimethoxysilane, but is not limited thereto.

[0118] The silane coupling agent may be contained in the composition for adhesive films in an amount of 0 to 5 parts by weight, for example 0.1 to 3 parts by weight, based on the solid content, per 100 parts by weight of the (meth)acrylic copolymer or the cured product of the (meth)acrylic copolymer. Within this range, other physical properties of the adhesive film are not affected, and the adhesive strength of the adhesive film to the adherend can be increased.

[0119] The silane coupling agent may be contained in the pressure-sensitive adhesive film in an amount of 0 to 5% by weight, specifically 0.1 to 3% by weight. Within this range, other physical properties of the pressure-sensitive adhesive film are not affected, and the adhesive strength of the pressure-sensitive adhesive film to the adherend can be increased.

[0120] The adhesive film may further contain conventional additives such as antistatic agents, surfactants, curing accelerators, ionic liquids, lithium salts, inorganic fillers, softeners, molecular weight regulators, antioxidants, antiaging agents, stabilizers, tackifier resins, modifying resins (polyol resins, phenolic resins, acrylic resins, polyester resins, polyolefin resins, epoxy resins, epoxidized polybutadiene resins, etc.), leveling agents, defoamers, plasticizers, dyes, pigments (coloring pigments, extender pigments, etc.), treatment agents, fluorescent brighteners, dispersants, heat stabilizers, light stabilizers, flocculants, and lubricants.

[0121] The additive may be contained in the adhesive film at 10% by weight or less, specifically 0.01% by weight to 10% by weight, specifically 0.01% by weight to 1% by weight. Within this range, the adhesive strength and reliability of the adhesive film are not affected, and the additive can exert its effect.

[0122] The adhesive film may have a thickness of 200 μm or less, for example, more than 0 μm and not more than 200 μm, such as 150 μm to 200 μm. With a thickness in this range, the film can be used in optical display devices.

[0123] The adhesive film can be produced by coating one surface of a substrate film with a composition for adhesive film to form a coating layer, and drying and photocuring the coating layer. In order to prevent foreign matter from being embedded in the adhesive film after the coating layer is aged, a release film can be further attached to one surface of the adhesive film. The drying can include, but is not limited to, a process of treating the coating layer at 100°C to 150°C for 0.5 to 5 minutes. If drying is not necessarily required, it can be omitted. The photocuring can be partial curing. In this case, the amount of light needs to be adjusted so that the photocuring rate of the adhesive film according to Equation 2 is not 100%, that is, the adhesive film is not completely cured.

[0124] Hereinafter, a pressure-sensitive adhesive film according to another embodiment will be described.

[0125] The adhesive film includes a (meth)acrylic copolymer, a chain transfer agent, a photoinitiator, a mixture of UV absorbers, and organic nanoparticles, and the mixture of UV absorbers includes an indole-based UV absorber as a first UV absorber, and one or more of 2-hydroxyphenyl-s-triazine as a triazine-based UV absorber and 2-(5-chloro-2H-benzotriazol-2-yl)-6-(1,1-dimethylethyl)-4-methylphenol as a benzotriazole-based UV absorber as a second UV absorber.

[0126] The adhesive film is substantially the same as the adhesive film described above, except that it further contains organic nanoparticles. The further inclusion of organic nanoparticles does not affect the physical properties of the adhesive film described above. Instead, the organic nanoparticles can improve the impact resistance of the adhesive film.

[0127] The organic nanoparticles can increase the impact resistance of an organic light emitting device panel that does not have a polarizer on its upper surface.

[0128] The organic nanoparticles may have an average particle size of 10 nm to 400 nm, specifically 10 nm to 300 nm, more specifically 30 nm to 280 nm, and even more specifically 50 nm to 280 nm. In this range, the folding of the adhesive film is not affected, and the total light transmittance in the visible light region is 90% or more, improving the transparency of the adhesive film.

[0129] The organic nanoparticles may have a refractive index of 1.35 to 1.70, specifically 1.40 to 1.60. Within this range, the transparency of the adhesive film is excellent.

[0130] The organic nanoparticles may include simple nanoparticles such as core-shell type and bead type, but are not limited thereto. In the case of the core-shell type, the core and shell may satisfy the following formula 4. In other words, both the core and shell of the organic nanoparticles may form an organic material. When the nanoparticles have such a particle shape, the adhesive film has good folding properties and is effective in balancing the physical properties of elasticity and flexibility.

[0131] [Formula 4] Tg(c) <Tg(s) (In Equation 4, Tg(c) is the glass transition temperature of the core (unit: °C), and Tg(s) is the glass transition temperature of the shell (unit: °C).)

[0132] As used herein, "shell" refers to the outermost layer in an organic nanoparticle. The core may be a single spherical particle. However, the core may also include an additional layer covering the spherical particle, provided that the core has the glass transition temperature.

[0133] Specifically, the glass transition temperature of the core may be -150°C to 10°C, specifically -150°C to -5°C, and more specifically -150°C to -20°C. Within this range, the adhesive film exhibits a viscoelastic effect at low temperature and / or room temperature. The core may contain one or more of polyalkyl acrylate, polysiloxane, or polybutadiene having this glass transition temperature.

[0134] The polyalkyl acrylates may include, but are not necessarily limited to, one or more of polymethyl acrylate, polyethyl acrylate, polypropyl acrylate, polybutyl acrylate, polyisopropyl acrylate, polyhexyl acrylate, polyhexyl methacrylate, polyethylhexyl acrylate and polyethylhexyl methacrylate, polysiloxanes.

[0135] The polysiloxane may be, for example, an organosiloxane (co)polymer. The organosiloxane (co)polymer may be one that is not crosslinked, or a crosslinked (co)polymer may be used. For impact resistance and colorability, a crosslinked organosiloxane (co)polymer may be used. Specifically, crosslinked dimethylsiloxane, methylphenylsiloxane, diphenylsiloxane, or a mixture of two or more thereof may be used as the crosslinked organosiloxane. By using a copolymerized form of two or more organosiloxanes, the refractive index can be adjusted to 1.41 to 1.50.

[0136] The crosslinked state of the organosiloxane (co)polymer can be judged by the degree of dissolution in various organic solvents. The deeper the crosslinked state, the smaller the degree of dissolution in the solvent. Acetone, toluene, etc. can be used as a solvent for judging the crosslinked state, and specifically, the organosiloxane (co)polymer may have a portion that is not dissolved in acetone or toluene. The insoluble component in toluene of the organosiloxane copolymer may be 30% or more.

[0137] Furthermore, the organosiloxane (co)polymer may further include an alkyl acrylate crosslinked polymer. As the alkyl acrylate crosslinked polymer, methyl acrylate, ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, etc. may be used. For example, n-butyl acrylate or 2-ethylhexyl acrylate, which has a low glass transition temperature, may be used.

[0138] Specifically, the glass transition temperature of the shell may be 15°C to 150°C, specifically 35°C to 150°C, more specifically 50°C to 140°C. In this range, the dispersibility of the organic nanoparticles in the acrylic copolymer is excellent. The shell may contain a polyalkyl methacrylate having a glass transition temperature. For example, the shell may contain one or more of polymethyl methacrylate (PMMA), polyethyl methacrylate, polypropyl methacrylate, polybutyl methacrylate, polyisopropyl methacrylate, polyisobutyl methacrylate, and polycyclohexyl methacrylate, but is not necessarily limited thereto.

[0139] The core may be contained in the organic nanoparticles at 30% by weight to 99% by weight, specifically 40% by weight to 95% by weight, more specifically 50% by weight to 90% by weight. In this range, the folding property of the adhesive film is improved over a wide temperature range. The shell may be contained in the organic nanoparticles at 1% by weight to 70% by weight, specifically 5% by weight to 60% by weight, more specifically 10% by weight to 50% by weight. In this range, the folding property of the adhesive film is improved over a wide temperature range.

[0140] The organic nanoparticles may be contained in the adhesive film composition in an amount of 0 to 10 parts by weight, for example 0.1 to 9 parts by weight, based on the solid content, per 100 parts by weight of the (meth)acrylic copolymer or the cured product of the (meth)acrylic copolymer. Within this range, the impact resistance of the adhesive film can be improved, and an increase in the haze of the adhesive film due to the addition of an excessive amount can be prevented.

[0141] The organic nanoparticles may be contained in the adhesive film at 0.1% by weight to 20% by weight, specifically 0.5% by weight to 10% by weight, or 0.5% by weight to 8% by weight. Within this range, the impact resistance of the adhesive film can be improved, and an increase in the haze of the adhesive film due to the addition of an excessive amount can be prevented.

[0142] The organic nanoparticles can be produced by conventional emulsion polymerization, suspension polymerization, or solution polymerization methods.

[0143] Hereinafter, an optical display device according to an embodiment of the present invention will be described.

[0144] The optical display device includes the adhesive film according to the present invention. Preferably, the optical display device includes a light-emitting element panel and an adhesive film laminated on the light-emitting surface of the light-emitting element panel, and the adhesive film may be a post-cured product of the adhesive film produced by post-curing the adhesive film of the present invention. The post-cured product of the adhesive film can provide the above-mentioned light transmittance at a wavelength of 380 nm or 405 nm, storage modulus at 25°C to 60°C, and peel strength from a glass plate. Therefore, the cured product of the adhesive film replaces the polarizing plate, and the optical display device becomes an optical display device without a polarizing plate. EXAMPLES

[0145] The present invention will be described in more detail with reference to the following preferred embodiments, which are merely illustrative of the present invention and should not be construed as limiting the present invention in any way.

[0146] Example 1 Into a reactor, 100 parts by weight of a monomer mixture containing 40 parts by weight of 2-ethylhexyl acrylate, 20 parts by weight of 4-hydroxybutyl acrylate, 10 parts by weight of acryloylmorpholine, 10 parts by weight of dihydrodicyclopentadienyl acrylate (DCPA), and 20 parts by weight of benzyl acrylate was placed, and the solvent toluene was added. A photoinitiator was added, and the mixture was polymerized by stirring for 30 minutes while purging with nitrogen to produce a (meth)acrylic copolymer derived from 2-ethylhexyl acrylate, 4-hydroxybutyl acrylate, acryloylmorpholine, dihydrodicyclopentadienyl acrylate, and benzyl acrylate.

[0147] Based on the solid content, 100 parts by weight of the prepared (meth)acrylic copolymer, 0.06 parts by weight of a crosslinking agent, 0.3 parts by weight of a photoinitiator, 0.13 parts by weight of an indole-based UV absorber, 0.10 parts by weight of Tinuvin 477 (BASF), 0.15 parts by weight of a chain transfer agent, and 0.10 parts by weight of a silane coupling agent were mixed to prepare a composition for adhesive film.

[0148] The adhesive film composition thus produced was applied to one side of a polyethylene terephthalate film (TU73A, SKC, thickness: 75 μm, not release-treated) as a release film in a thickness of 200 μm, and then irradiated with UV light of 315 nm to 400 nm in wavelength at 1000 mJ / cm using a BL lamp (black light lamp). 2 By irradiating the adhesive film with a light amount of 10 ...

[0149] Examples 2 to 6 An adhesive film was prepared in the same manner as in Example 1, except that the type and / or content of each component was changed as shown in Table 1 below.

[0150] Comparative Example 1 to Comparative Example 4 An adhesive film was prepared in the same manner as in Example 1, except that the type and / or content of each component was changed as shown in Table 1 below.

[0151] [Table 1]

[0152] *In Table 1, crosslinker: hexanediol diacrylate, Photoinitiator: TPO (BASF) Chain transfer agent: 2-ethylhexyl-3-mercaptopropionate (EHMP, TCI) Silane coupling agent: KBM-403 (Shinetsu) Organic particles: Core-shell organic nanoparticles manufactured by emulsion polymerization. The core is polybutyl acrylate and the shell is polymethyl methacrylate. The shell is 35% by weight in the organic nanoparticles, and the core is 65% by weight in the organic nanoparticles. The core-shell organic nanoparticles have an average particle size (D50) of 100 nm and a refractive index of 1.48. UA-3912 (Orient): Indole-based UV absorber Tinuvin 477 (BASF): Triazine UV absorber Tinuvin 326 (BASF): Benzotriazole UV absorber Tinuvin 479 (BASF): Triazine UV absorber (has a different chemical structure from Tinuvin 477) Tinuvin 460 (BASF): Triazine-based UV absorber (Tinuvin 477 Tinuvin 384-2 (BASF): Benzotriazole UV absorber (has a different chemical structure from Tinuvin 326)

[0153] Equation 3: Weight ratio of (content of initiator) / (total content of triazine-based UV absorber and benzotriazole-based UV absorber) in adhesive film

[0154] The adhesive films produced in the examples and comparative examples were evaluated for the physical properties shown in Table 2 below, and the results are shown in Table 2 below.

[0155] (1) Storage modulus (unit: kPa): The storage modulus was measured using a dynamic viscoelasticity measuring device DHR-3 (TA Co.) under auto strain conditions of axial force: 1.0N, sensitivity: 0.1N, frequency: 1.0Hz, and strain: 1.0%. The adhesive film was laminated to a thickness of 800μm, and the laminate was punched with a punch having a diameter of 8mm to produce a circular specimen, which was then measured. The storage modulus was measured at a temperature rise rate of -60℃~90℃ and 5℃ / min, and the storage modulus was calculated at 25℃ and 60℃.

[0156] (2) Peeling force against glass plate (unit: gf / inch): The peeling force against non-alkali glass plate was measured. A plasma-treated PET film (NK-P50DP) was attached to one side of the adhesive film produced in the examples and comparative examples, and cut into a size of 2.5 cm x 10 cm (horizontal x vertical). After peeling off the release PET film, it was attached to a non-alkali glass plate (soda-lime glass plate) to produce a test piece laminated in the order of non-alkali glass plate-adhesive film-plasma-treated PET film. The test piece was fixed to a peel strength measuring device, TA (Texture Analyer) Instrument, and the peeling force was measured when the adhesive film and PET film laminate were peeled off from the non-alkali glass plate at a peeling speed of 300 mm / min and a peeling angle of 180° at 25°C.

[0157] (3) Light transmittance (unit: %) and transmission b*: The light transmittance was measured for an alkali-free glass plate using a light transmittance meter V650 (JASCO) to determine the baseline. After peeling the release film from the adhesive film, it was attached to an alkali-free glass plate to prepare a test piece for measuring light transmittance. The light transmittance of the test piece was measured using a light transmittance meter V650 (JASCO). The transmission b* value was also measured in the same manner as the light transmittance.

[0158] (4) Impact resistance (unit: cm): An adhesive film from which the release film had been removed was attached to one side of an organic light-emitting element panel (containing an organic light-emitting element light-emitting layer between both substrates), and a PET film (SH86, SKC, thickness: 50 μm) was attached to the other side of the adhesive film. A BIC pen was then dropped on the panel, and the drop height was increased and the height at which the PET film first became dented and / or damaged was measured.

[0159] [Table 2]

[0160] The adhesive films produced in the examples and comparative examples were exposed to 1000 mJ / cm 2 UV light with wavelengths of 315 nm to 400 nm using a metal halide lamp. 2 A post-cured adhesive film (completely cured state, photocuring rate according to Equation 2: 100%, thickness: 200 μm) was produced by irradiating with a light amount of 1000 μm. The physical properties of the post-cured adhesive film were evaluated using the same method as described in Table 2, and the results are shown in Table 3 below.

[0161] [Table 3]

[0162] As shown in Tables 2 and 3, the adhesive film of the present invention has a light transmittance of 1% or less at wavelengths of 380 nm and 3% or less at wavelengths of 405 nm, respectively, and even after post-curing, the light transmittance is 1% or less and 3% or less at wavelengths of 380 nm and 405 nm, respectively, so it is expected to protect the organic light-emitting element from damage caused by UV. In addition, although the adhesive film is in a partially cured state, by satisfying all of the above-mentioned elastic modulus and peel strength, it can be adhered to the adherend with high reliability, and the viscoelasticity after post-curing is improved, resulting in excellent bending reliability.

[0163] On the other hand, the adhesive films of the comparative examples could not achieve all of the above-mentioned effects.

[0164] Simple modifications or alterations of the present invention can be easily implemented by a person having ordinary skill in the art, and all such modifications and alterations can be considered to be included within the scope of the present invention.

Claims

1. a mixture of a (meth)acrylic copolymer, a chain transfer agent, a photoinitiator, and a UV absorber; The mixture of UV absorbers includes an indole UV absorber as a first UV absorber, and one or more of a 2-hydroxyphenyl-s-triazine triazine UV absorber and a benzotriazole UV absorber, 2-(5-chloro-2H-benzotriazol-2-yl)-6-(1,1-dimethylethyl)-4-methylphenol, as a second UV absorber.

2. The adhesive film according to claim 1, wherein the ratio of the following formula 1 is 80% or more and less than 100%: [Formula 1] Storage modulus ratio = A / B x 100 (In the above formula 1, A is the storage modulus (unit: kPa) of the adhesive film at 25 ° C., B is the storage modulus (unit: kPa) of the post-cured adhesive film at 25°C.

3. The pressure-sensitive adhesive film according to claim 1 , wherein the pressure-sensitive adhesive film has a light transmittance of 1% or less at a wavelength of 380 nm.

4. The pressure-sensitive adhesive film according to claim 1 , wherein the pressure-sensitive adhesive film has a light transmittance of 3% or less at a wavelength of 405 nm.

5. The pressure-sensitive adhesive film according to claim 1 , wherein the pressure-sensitive adhesive film has a storage modulus of 150 kPa or less at 25° C. and a storage modulus of 100 kPa or less at 60° C.

6. The adhesive film according to claim 1, wherein the indole UV absorber comprises a compound of the following general formula 1: [General formula 1] 【Chemistry 1】 (In the above general formula 1, R 1 represents hydrogen or a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms; R 2 represents hydrogen or a substituted or unsubstituted aryl group having 6 to 20 carbon atoms; R 3 represents hydrogen or a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms; R 4 represents hydrogen, a cyano group (CN), or a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms; R 5 is a cyano group or -(C=O)O-R 6 (At this time, R 6 represents a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 20 carbon atoms).

7. The adhesive film according to claim 1 , wherein the indole UV absorber is contained in the adhesive film in an amount of 0.01% by weight to 10% by weight.

8. The adhesive film according to claim 1 , wherein the second UV absorber is contained in the adhesive film in an amount of 0.01% by weight to 5% by weight.

9. The adhesive film according to claim 1, wherein the weight ratio of the following formula 3 in the adhesive film is 0.06 to 6: [Formula 3] Weight ratio = photoinitiator / second UV absorber.

10. The adhesive film according to claim 1 , wherein the sum of the first UV absorber and the second UV absorber is 95% by weight or more in the mixture of UV absorbers.

11. The (meth)acrylic copolymer is a copolymer of a monomer mixture containing an alkyl group-containing (meth)acrylic monomer, a hydroxyl group-containing (meth)acrylic monomer, and a (meth)acrylic or vinyl monomer having a high glass transition temperature of a homopolymer. The pressure-sensitive adhesive film according to claim 1.

12. The (meth)acrylic or vinyl monomer having a high glass transition temperature of the homopolymer has a higher glass transition temperature than the glass transition temperatures of the homopolymers of the alkyl group-containing (meth)acrylic monomer and the hydroxyl group-containing (meth)acrylic monomer, respectively. The pressure-sensitive adhesive film according to claim 11.

13. The (meth)acrylic or vinyl monomer having a high homopolymer glass transition temperature includes at least one of a nitrogen-containing (meth)acrylic or vinyl monomer and an alicyclic group-containing (meth)acrylic or vinyl monomer. The pressure-sensitive adhesive film according to claim 11.

14. The (meth)acrylic or vinyl monomer having a high glass transition temperature of the homopolymer includes at least one of (meth)acryloylmorpholine, N-vinylpyrrolidone, dihydrodicyclopentadienyl acrylate, and isobornyl (meth)acrylate. The pressure-sensitive adhesive film according to claim 11.

15. The pressure-sensitive adhesive film according to claim 11 , wherein the monomer mixture further comprises an aromatic group-containing (meth)acrylic monomer.

16. The adhesive film is 100 parts by weight of the (meth)acrylic copolymer, 0.01 parts by weight to 2 parts by weight of the chain transfer agent, 0.1 parts by weight to 2 parts by weight of the photoinitiator; 0.01 parts by weight to 0.5 parts by weight of the first UV absorber, and The adhesive film according to claim 1, which is formed from a composition for adhesive films comprising 0.01 to 5 parts by weight of the second UV absorbent.

17. The adhesive film according to claim 1 , further comprising organic nanoparticles.

18. The adhesive film according to claim 17, wherein the organic nanoparticles are of a core-shell type and satisfy the following mathematical formula 4: [Formula 4] Tg(c)<Tg(s) (In the above formula 4, Tg(c) is the glass transition temperature (unit: ° C.) of the core, and Tg(s) is the glass transition temperature (unit: ° C.) of the shell.)

19. The pressure-sensitive adhesive film according to claim 1 , further comprising at least one of a crosslinking agent and a silane coupling agent.

20. An optical display device comprising a post-cured product of the pressure-sensitive adhesive film according to claim 1 .

21. 21. The optical display of claim 20, wherein the optical display does not include a polarizer.

Citation Information

Patent Citations

  • KR2007-0055363